Differential decay of intact and defective proviral DNA in HIV-1–infected individuals on suppressive antiretroviral therapy - Peluso, Michael J. (JCI Insight, 2020)
BACKGROUND: The relative stabilities of the intact and defective HIV genomes over time during effective antiretroviral therapy (ART) have not been fully characterized. METHODS: We used the intact proviral DNA assay (IPDA) to estimate the rate of change of intact and defective proviruses in HIV-infected adults on ART. We used linear spline models with a knot at seven years and a random intercept and slope up to the knot. We estimated the influence of covariates on rates of change. RESULTS: We studied 81 individuals for a median of 7.3 (IQR 5.9-9.6) years. Intact genomes declined more rapidly from initial suppression through seven years (15.7% per year decline; 95% CI -22.8%, -8.0%) and more slowly after seven years (3.6% per year; 95% CI -8.1%, +1.1%). The estimated half-life of the reservoir was 4.0 years (95% CI 2.7-8.3) until year seven and 18.7 years (95% CI 8.2-infinite) thereafter. There was substantial variability between individuals in the rate of decline until year seven. Intact provirus declined more rapidly than defective provirus (P < 0.001) and showed a faster decline in individuals with higher CD4(+) T cell nadirs. CONCLUSION: The biology of the replication-competent (intact) reservoir differs from that of the replication-incompetent (non-intact) pool of proviruses. The IPDA will likely be informative when investigating the impact of interventions targeting the reservoir. FUNDING: Delaney AIDS Research Enterprise, UCSF/Gladstone Institute of Virology & Immunology CFAR, CFAR Network of Integrated Systems, amfAR Institute for HIV Cure Research, I4C and Beat-HIV Collaboratories, Howard Hughes Medical Institute, Gilead Sciences, Bill and Melinda Gates Foundation.